The numerati - Baker, Stephen, 1955- (Houghton Mifflin, 2008)
"The Numerati" shows how a powerful new endeavor--the mathematical modeling of humanity--stands to transform everyone's daily life.
Keywords: informační společnost; informační technologie -- sociologické aspekty; dolování dat -- sociologické aspekty; information society; information technology -- sociological aspects; data mining -- sociological aspects; studie; studies